4p-12=-3+p

Simple and best practice solution for 4p-12=-3+p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4p-12=-3+p equation:


Simplifying
4p + -12 = -3 + p

Reorder the terms:
-12 + 4p = -3 + p

Solving
-12 + 4p = -3 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-12 + 4p + -1p = -3 + p + -1p

Combine like terms: 4p + -1p = 3p
-12 + 3p = -3 + p + -1p

Combine like terms: p + -1p = 0
-12 + 3p = -3 + 0
-12 + 3p = -3

Add '12' to each side of the equation.
-12 + 12 + 3p = -3 + 12

Combine like terms: -12 + 12 = 0
0 + 3p = -3 + 12
3p = -3 + 12

Combine like terms: -3 + 12 = 9
3p = 9

Divide each side by '3'.
p = 3

Simplifying
p = 3

See similar equations:

| -7x-10x=-85 | | 4x-10x=70 | | -5x-15=-95 | | -60=3+9x | | (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= | | 9x+12y+15= | | 6a-18b+12c= | | 12a-28b+10c= | | 40=5w-15 | | 7x-7y-7z= | | 5x-5y+10z= | | 4d^2+29d-60=0 | | 45r^2-5=0 | | 45r^2-5=f | | 25x^2+16=y | | 6x(x-2)=0 |

Equations solver categories